Diabetic retinopathy as a potential risk factor for ptosis: A 13-year nationwide population-based cohort study in Taiwan - Lin, Chun-Ju; Hsu, Alan Y.; Tien, Peng-Tai; Chang, Cheng-Hsien; Lai, Chun-Ting; Hsia, Ning-Yi; Yang, Yu-Cih; Bair, Henry; Chen, Huan-Sheng; Chen, Wen-Lu; Tsai, Yi-Yu (Frontiers in Epidemiology, 2023)
Purpose: To determine the risk of ptosis among diabetic retinopathy (DR) patients Methods: This is a population-based, retrospective, matched-cohort study where DR patients were recruited from the Taiwan National Health Insurance Research Database (NHIRD) to investigate the risk of developing ptosis. Preexisting co-factors of interest included smoking status and medical comorbidities of hyperlipidemia and hypertension. Statistical analysis was performed using T-test, Cox-proportional hazard ratios adjusted for comorbidities (aHR), Wilcoxon rank sum test, Kaplan-Meier estimators, and log rank tests. Results: Follow-up data of 9,494 patients with DR and 37,976 matched control cohort (non-DR) from 2000 to 2012 were analyzed. DR patients were found to have significantly increased risk of developing ptosis (adjusted hazard ratio (HR) [95% CI]: 2.76 [1.74-4.38], p < 0.001) when compared to the control cohort. Female gender and adults of all age groups were found to increase the risk of developing ptosis. When stratified by co-factors of interest, increased risk of ptosis was seen among DR patients and this risk was also increased when associated with non-smoking status. Furthermore, DR patients was also found to have increased risk of developing ptosis when compared to matched controls, regardless of whether they had medical comorbidities of lipid metabolism disorders or hypertension. Conclusions: In this large-scale study using real-world data, our results showed that DR patients were found to have increased risk of developing ptosis. Female gender, adult age, and non-smokers were also shown to increase the risk of ptosis among DR patients. This has implications towards the care of diabetic patients, complications such as ptosis should be properly screened for when encountering such patients. Before ptosis surgery, the possibility of underlying diabetes or DR should be also scrutinized and treated properly to avoid undesirable postoperative dissension.